Temporary Storage of the Human Nasal Tissue and Cell Sheet for Wound Repair - Kasai, Yoshiyuki; Morino, Tsunetaro; Dobashi, Izumi; Mori, Eri; Yamamoto, Kazuhisa; Kojima, Hiromi (Frontiers in Bioengineering and Biotechnology, 2021)
Temporary storage of nasal tissues and nasal cell sheets, which entails transportation between hospitals and cell culture facilities, is an important issue in regenerative medicine. Herein, we investigated the preservation of chilled and frozen nasal tissues and expiry dates of ready-to-use nasal cell sheets. Although the cell number in preserved tissues was lower than that in fresh tissue, nasal cell sheets could be fabricated from tissues that had been refrigerated for 5 days and frozen–thawed over 5 days. Moreover, the nasal mucosal cell sheets were preserved in a non-hazardous buffer. The cell number, viability, and structure were not maintained in saline containing E-cadherin for 2 days; however, these were maintained in Hank’s balanced salt solution for 2 days, but not for 5 days. To assess the proliferation capacity of cells in the stored cell sheets, we performed cell sheet grafting assays in vitro. Cell sheets stored in Hank’s balanced salt solution for 2 days adhered to collagen gel and expanded normally. Our results show that nasal tissues can be stored temporarily in refrigerators or deep freezers, and Hank’s balanced salt solution can be used for preservation of ready-to-use cell sheets for a few days.